ANALISA PENAMBAHAN KAWAT GALVANIS TERHADAP NILAI KUAT TEKAN BETON SERAT - Denie Chandra; Rifky Herando (JURNAL REKAYASA, 2025)
Concrete quality is determined by the materials used to form it. This research, a continuation of previous research, presents the results of a laboratory study on the effect of adding galvanized wire as a concrete forming material. This study was conducted to determine the value of galvanized wire as a coarse aggregate substitute and the mechanical properties of normal concrete on the design compressive strength fc'25. Test specimens were prepared at the Laboratory of the Faculty of Civil Engineering, Indo Global Mandiri University, Palembang. The test specimens were prepared (experimentally) with variations in the addition of galvanized wire to the cement weight of 2%, 4%, and 6% of the normal concrete Job Mix Formula. The specimens were cured by soaking until the compressive strength test was conducted at 7, 14, and 28 days. The results of the experimental study, with variations in the percentage weight of galvanized wire, yielded an average compressive strength of 27.38 MPa with the addition of galvanized wire material at 6% of the cement weight